2011
DOI: 10.1007/s11092-011-9126-2
|View full text |Cite
|
Sign up to set email alerts
|

Taking the grading leniency story to the edge. The influence of student, teacher, and course characteristics on student evaluations of teaching in higher education

Abstract: The use of student evaluation of teaching (SET) to evaluate and improve teaching is widespread amongst institutions of higher education. Many authors have searched for a conclusive understanding about the influence of student, course, and teacher characteristics on SET. One hotly debated discussion concerns the interpretation of the positive and statistically significant relationship that has been found between course grades and SET scores. In addition to reviewing the literature, the main purpose of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 54 publications
2
42
0
1
Order By: Relevance
“…The correlation between teaching evaluation scores and whole class average grades is stronger than the correlation between individual student's grades. The results are similar to the research results of Hoefer, Yurkiewicz, and Byrne (2012), Brockx, Spooren, and Mortelmans (2011), and Johnson, Narayanan, and Sawaya (2013. The study also found that variation of examined correlations existed among different curricula conditions, which is similar to the research results of Griffin, Hilton, Plummer, and Barret (2014).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The correlation between teaching evaluation scores and whole class average grades is stronger than the correlation between individual student's grades. The results are similar to the research results of Hoefer, Yurkiewicz, and Byrne (2012), Brockx, Spooren, and Mortelmans (2011), and Johnson, Narayanan, and Sawaya (2013. The study also found that variation of examined correlations existed among different curricula conditions, which is similar to the research results of Griffin, Hilton, Plummer, and Barret (2014).…”
Section: Discussionsupporting
confidence: 89%
“…They found that there was a significant but relatively small correlation between the teaching evaluation scores and average students' grades. Brockx, Spooren, and Mortelmans (2011) examined the influence of course grades on teaching evaluation socres. The results showed positive significant relationships between course grades and teaching evaluation scores.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Turning to the critical literature regarding SETs, some authors have focused on their gender bias (Boring, 2017), whilst other research has focused on the lack of The UK National Student Survey 539 validity of national SETs by critically interrogating the correlation between higher grades and higher marks (Brockx et al, 2011). A more significant body of work has critiqued SETs in the context of the ongoing 'marketisation of higher education' (Jones-Devitt & Samiei, 2011;Molesworth et al, 2011) and neo-liberalism (Grimmett et al, 2009;McGettigan, 2013;Giroux, 2014).…”
Section: Context: the National Student Surveymentioning
confidence: 99%
“…Although, some studies have shown positive reliability and validity of SET (Thornton, Adams & Sepehri, 2010) others have shown that SET does not accurately measure teaching effectiveness (Weinberg, Hashimoto & Fleisher, 2009;Brockx, Spooren & Mortelmans, 2011;Sheppard, 2013).…”
Section: Factors That Affect Students' Evaluationmentioning
confidence: 99%